Efficiency of Chamomile Essential Oils on Sleeping Quality of First-year University Students (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: This is the quasi-experimental research proposed to study the efficiency of chamomile essentialoils on sleeping quality of the first-year university student.Methods: The sample was selected on 20 students with poor sleeping quality. The study was done weekly in2 weeks, intervened with chamomile essential oil. Research tools were the 3-parts questionnaires includingpersonal information, quality of sleep and environmentally influencing sleep. Data were analyzed instatistically parameters.Results: The sleeping quality of the 1st year university students in chamomile group, compare mean andstandard deviation of experimental group found that the mean pre-test sleep quality was M = 80.20, SD =6.65, with poor sleep quality overall and after 2 weeks of trial participation M = 55.65, SD = 10.32, whichhad moderate sleep quality. In experiment with the experimental group, it was found that after 2 weeks ofusing chamomile essential oil, the sleep quality of the experimental group improved. According to statisticalcomparison, t = 2.494, p-value = .022.Conclusion: This study uses of chamomile essential oil showed an improvement in the sleep effect of theexperimental group. To be concluded that chamomile essential oils improved the sleeping quality significantlyas the well-known lavender essential oils. However further study in larger group is recommended.
Keywords: chamomile oils, sleeping quality, mental health, university students.